Use of repurposed and adjuvant drugs in hospital patients with covid-19: multinational network cohort study. (11th May 2021) - Prats-Uribe, Albert; Sena, Anthony G; Lai, Lana Yin Hui; Ahmed, Waheed-Ul-Rahman; Alghoul, Heba; Alser, Osaid; Alshammari, Thamir M; Areia, Carlos; Carter, William; Casajust, Paula; Dawoud, Dalia; Golozar, Asieh; et al.
Abstract: Objective: To investigate the use of repurposed and adjuvant drugs in patients admitted to hospital with covid-19 across three continents. Design: Multinational network cohort study. Setting: Hospital electronic health records from the United States, Spain, and China, and nationwide claims data from South Korea. Participants: 303 264 patients admitted to hospital with covid-19 from January 2020 to December 2020. Main outcome measures: Prescriptions or dispensations of any drug on or 30 days after the date of hospital admission for covid-19. Results: Of the 303 264 patients included, 290 131 were from the US, 7599 from South Korea, 5230 from Spain, and 304 from China. 3455 drugs were identified. Common repurposed drugs were hydroxychloroquine (used in from <5 (<2%) patients in China to 2165 (85.1%) in Spain), azithromycin (from 15 (4.9%) in China to 1473 (57.9%) in Spain), combined lopinavir and ritonavir (from 156 (<2%) in the VA-OMOP US to 2, 652 (34.9%) in South Korea and 1285 (50.5%) in Spain), and umifenovir (0% in the US, South Korea, and Spain and 238 (78.3%) in China). Use of adjunctive drugs varied greatly, with the five most used treatments being enoxaparin, fluoroquinolones, ceftriaxone, vitamin D, and corticosteroids. Hydroxychloroquine use increased rapidly from March to April 2020 but declined steeply in May to June and remained low for the rest of the year. The use of dexamethasone and corticosteroids increased steadily during 2020. Conclusions: Multiple drugs were used in the first few months of the covid-19 pandemic, with substantial geographical and temporal variation. Hydroxychloroquine, azithromycin, lopinavir-ritonavir, and umifenovir (in China only) were the most prescribed repurposed drugs. Antithrombotics, antibiotics, H2 receptor antagonists, and corticosteroids were often used as adjunctive treatments. Research is needed on the comparative risk and benefit of these treatments in the management of covid-19.